Efektifitas Metode Bercerita dalam Pembelajaran PAK - Jhoni Lagun Siang (Pascasarjana IAKN Manado, 2023)
The PAK method is a service, an effective work, which we do for God and fellow human beings, so that the two parties serve each other, the meaning is a method that helps students in learning sir, to really learn God's word where changes occur, both in his knowledge, attitudes and values as well as his conduct according to the word of God. However, Homringhausen reminded that the method is only a way or a way or not an end in itself, so we cannot absolute the method. This means that our main goal is how students in PAK learning maximally learn from God's Word. Based on the results of the author's observations, at the end of PAK lessons which were conducted using this storytelling method, the teacher did not provide applications to students' real lives. This has an impact on the quality of life of students who are not getting better. Based on the results of the researchers' observations of student behavior after participating in PAK learning, it was very much dominated by one another's bad behavior. The storytelling method must be able to stimulate the imagination of students, by means of delivery that seems to live in the story being told. The result of the author's observation is that Eklesia Vocational High School teachers are not able to tell stories in a style, expression, expression that seems to live in the story. That's why learning becomes ineffective.